Tetrazolium Test for the Seeds of Acacia nilotica Willd. Ex. Del - Gera, Neelu; Gera, Mohit; Purohit, Mamta (Indian Forester, 1998)
The paper deals with the standardization of evaluation criteria for the tetrazolium test on the seeds of Acacia nilotica Willd.ex.Del. Chipping of seed coat was found necessary for satisfactory imbibition and staining. Seeds were soaked in distilled water for 24 hours followed by soaking in 1% 'ITZ solution and incubated at 30Â°C in dark for 24 hours. Six staining patterns were recognized. Root mean square method was applied to determine the viable categories. Three staining patterns represented viable and three non-viable seeds.